Bright Microresonator Solitons in the Normal Dispersion Regime - Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We report the first experimental observation of bright single soliton states in the normal dispersion regime of a microresonator. The soliton generation can be explained by higher order dispersion.
CRIS-Team Scopus Importer:2024-10-04